The GDR tomorrow : rethinking the East German legacy - Emery, Elizabeth HerausgeberIn VerfasserIn; Hines, Matthew HerausgeberIn VerfasserIn; Preuss, Evelyn 1970- HerausgeberIn VerfasserIn (Studies in modern German and Austrian literature, 2024)
"A unique experiment at the frontlines of the Cold War, the German Democratic Republic collapsed more than thirty years ago. But it did not simply vanish. Far from being a footnote in history, the state and its legacies continue to inform identities, politics, and culture today. Studies of surveillance and government control, individual agency and equal opportunity, informal networks, strategic alliances, and strategies subverting limitations on freedom of expression prompt us to rethink our conceptualizations of the GDR. Introducing the work of a new generation of researchers, this anthology applies such approaches to a wide range of examples from film, theatre, music, literature, radio, and law. The chapters explore and transgress temporal, national, and disciplinary boundaries. From these investigations emerges a pervasive pattern of informal, border-transcending spheres, subversive identity discourses, and effective agency. Drawing variously on concepts such as Eigen-Sinn, informal society, and alternative public spheres, the papers presented here highlight the relevance of GDR Studies looking forwards. More than a volume about just the past, The GDR Tomorrow holds implications for the future"--